Case analysis of imitative innovation in Chinese manufacturing SMEs: Products, features, barriers and competences for transition. Issue 4 (August 2015) - Yu, Xiubao; Yan, Jie; Assimakopoulos, Dimitris
Abstract: Instead of viewing imitation and innovation as two opposite extremes, this research views firms' new product development as a continuous spectrum in which pure imitation at the one end and original innovation at the other. Firms change their position gradually by means of continuous organizational learning and systematic improvement in R&D capability during the imitative innovation process. Novelty and originality of innovations were increased gradually, and finally firms are able to carry out original innovations with good novelty. This case study investigates how the Chinese manufacturing SMEs go through this process. Drawing upon a multiple case study approach, this research in particular addresses the following questions: How do Chinese firms transit from pure imitation to original innovation through imitative innovation? What barriers may firms encounter in each stage of the transition? What competences do firms need to develop in order to make the transition successfully? Through appropriate Chinese manufacturing SMEs design they may improve their innovation capability to enable support to governmental policy making.